Operative rates in acute diverticulitis with concurrent small bowel obstruction. Issue 1 (6th July 2022) - Glaser, Jeffrey; Farrell, Michael Steven; Caplan, Richard; Rubino, Matthew
Abstract : Background: The prevalence of diverticulitis has steadily increased during the past century. One possible complication of large bowel diverticulitis (LBD) is the concurrent development of a small bowel obstruction (SBO). The literature regarding these joint diagnoses is primarily limited to small case series from the 1950s. Consequently, no official recommendations or recent literature exists to guide decision making. Methods: This is a retrospective case–control study with 5:1 matching by demographics, comorbidities, and Hinchey classification of patients presenting with concomitant LBD and SBO and patients with LBD alone. The primary outcome assessed was the need for same admission surgical intervention. Results: Patients with concurrent LBD and SBO were more likely to require surgical intervention (OR 4.2, p<0.001) and more likely to receive an open operation than patients with only LBD (p<0.001). The length of stay (LOS) was longer for LBD with SBO (mean LOS +3.2 days, p=0.003). Discussion: Patients with concurrent LBD and SBO are more likely to fail non-operative management. Given this, along with their longer LOS and higher rate of open surgery, earlier surgical intervention may improve outcomes and reduce hospital LOS. Level of evidence: 4.